2003
DOI: 10.1046/j.1537-2995.2003.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Yersinia enterocolitica, Pseudomonas fluorescens, and Pseudomonas putida outgrowth in deliberately inoculated blood by a novel pathogen‐reduction process

Abstract: The INACTINE process effectively prevented the outgrowth of Y. enterocolitica, P. fluorescens, and P. putida deliberately inoculated into WBC-reduced CPD/AS-1 and CP2D/AS-3 RBCs. The results demonstrated the crucial bactericidal role of PEN110 in the INACTINE process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…such as Y. enterocolitica and K. oxytoca. The growth kinetics were found to be comparable to those previously reported in the literature (29).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…such as Y. enterocolitica and K. oxytoca. The growth kinetics were found to be comparable to those previously reported in the literature (29).…”
Section: Discussionsupporting
confidence: 86%
“…The 4°C storage of RBCC strongly influences the reliability of being able to detect bacteria in contaminated units because the lag phase before the bacteria start to proliferate can be very long; even psychrophilic bacteria remain in a nondividing state for up to 10 days (29). The possibility of screening the donated unit for bacterial contamination immediately after collection is not practical, however, as the level of contaminating bacteria in the unit is, in the majority of cases, too low to ensure representation and detection in the test sample volume removed.…”
Section: Discussionmentioning
confidence: 99%
“…In another report, S marcescens contamination was attributed to bacteria in the saline solution used for the tranquilization of the donor cats. Also P fluorescens and P putida have been isolated from heparinized saline flush syringes, and from the phlebotomy site . In addition, leaky seals, damaged tubing, or micro‐punctures in collection bags have been linked to episodes of bacterial sepsis in human medicine .…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, ≥ 5·5 log 10 of Sindbis virus, ≥ 6·3 log 10 of VSV, ≥ 6·4 log 10 of BVDV, ≥ 6·5 log 10 of PRV, ≥ 6·0 log 10 of PPV, ≥ 6·5 log 10 of reovirus 3, ≥ 4·7 log 10 of Adenovirus‐2, ≥ 6·6 log 10 of vesicular exanthema of swine virus, ≥ 6·7 log 10 of foot and mouth disease virus, ≥ 6·7 log 10 of bluetongue virus, ≥ 7 log 10 of WNV, ≥ 5 log 10 DHBV, as well as ≥ 5·57 log 10 of extracellular HIV‐1 and ≥ 4·5 log 10 of cell‐associated HIV were inactivated [41–44]. Other studies demonstrated complete prevention of the outgrowth of 10–100 CFU/ml of Yersinia enterocolitica , Pseudomonas fluorescens and Pseudomonas putida during 42 ‐day storage of RBCs treated with 0·1% PEN110 for 24 h [45] and inactivation of ≥ 5·6 log10 of Acinetobacter lwoffii , ≥ 6·1 log 10 Acinetobacter johnsonii , ≥ 4 log 10 of Clostridium perfringens and ≥ 5 log 10 of Proprionibacterium acnes [46]. In another study, all detectable Babesia microti (by hamster assay), Plasmodium falciparum (by culture assay) and Trypanosoma cruzi (by culture and mouse assay) in blood were inactivated by treatment with 0·1% PEN110 at 23°C for 24 h [47].…”
Section: Akylating Agentsmentioning
confidence: 99%